Appraisal of adaptive neuro-fuzzy computing technique for estimating anti-obesity properties of a medicinal plant. Issue 1 (January 2015) - Kazemipoor, Mahnaz; Hajifaraji, Majid; Radzi, Che wan Jasimah Bt wan Mohamed; Shamshirband, Shahaboddin; Petković, Dalibor; Mat Kiah, Miss Laiha
Highlights Adaptive neuro-fuzzy computing technique in estimating the anti-obesity. Property of a potent medicinal plant in a clinical dietary intervention. Reduction in body mass index (BMI), body fat percentage, and body weight loss. Anti-obesity activities of caraway (Carum carvi) a traditional medicine on obese women.